2017
DOI: 10.1177/1948550617703170
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot of the Life as Lived

Abstract: Recent advances in mobile sensing technology provide innovative methods for understanding how individuals think, feel, and behave in vivo. Despite the utility of these new methods, as of yet, researchers have not been able to see the environments people encounter in their daily lives. In this article, we introduce wearable cameras as a new tool for sampling from participants’ everyday situations. Wearable cameras are small devices that capture pictures on a fixed interval (e.g., 30 s). This article discusses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Additionally, newer methods such as life logging (e.g. Brown, Blake, & Sherman, 2017) or the electronically activated recorder (Mehl, Pennebaker, Crow, Dabbs, & Price, 2001; Sun & Vazire, 2019) further extend the psychologists’ toolbox and provide us with a very powerful repertoire to examine personality dynamics. Although research on experience sampling methods and psychometric evaluation of data obtained in experience sampling has come a long way, many challenges remain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, newer methods such as life logging (e.g. Brown, Blake, & Sherman, 2017) or the electronically activated recorder (Mehl, Pennebaker, Crow, Dabbs, & Price, 2001; Sun & Vazire, 2019) further extend the psychologists’ toolbox and provide us with a very powerful repertoire to examine personality dynamics. Although research on experience sampling methods and psychometric evaluation of data obtained in experience sampling has come a long way, many challenges remain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, newer methods such as life logging (e.g., Brown, Blake, & Sherman, 2017) (Ziegler, 2014). We assume that our first overview of current practices, options, and methods will be somewhat outdated in a few years, but we look forward to the broad application of methods that only very few are currently thinking (or, via Twitter, heavily arguing) about.…”
Section: Discussionmentioning
confidence: 99%
“…The current study further illustrates how the EAR can provide a window into everyday social experiences. Recently, other research has shown how digital devices (e.g., smartphones, cameras) can successfully be used to collect data to examine psychological, behavioral, and health-related phenomena as they naturally occur in everyday life (e.g., Brown, Blake, & Sherman, 2017;Lathia, Sandstrom, Mascolo, & Rentfrow, 2017). Whereas past research often focused on between person comparisons, these new devices are particularly suited to disentangling the within-vs. between-person associations between social activity and well-being.…”
Section: Discussionmentioning
confidence: 99%